Comparison of Chinese and Western English language proficiency measures in transnational business degrees - Farley, Alan; Yang, Helen Hong; Min, Le (Lee); Ma, Shuang (Diana) (Language, culture, and curriculum, 2020)
This is the first empirical study to examine the comparative predictive power of Chinese national college English language program (CEP), a Western university's English for academic purpose (EAP) language program, a standardised English language proficiency (SELP) test, and business diploma for the academic performance of Chinese students in transnational business degree programs. The study analysed the academic results of 759 Chinese students who studied in the programs between 2006 and 2014. Crossover repeated measures design and multivariate regressions were used for analysis. Findings revealed that both CEP and EAP were good predictors of the performance in the first-year pathway diploma program. However, neither of them added any predictive power in later year degree subjects beyond the performance in the diploma program. There was a weak link between SELP and either CEP or EAP. This study also found that every student who failed the SELP test but had passed the diploma and the CEP and EAP programs successfully completed the degree. The study raises questions about English-speaking universities using SELP alone as an admission criteria. The study has implications for the admission policy of English-speaking universities.